Corrosion Experimental Research on Local Damage of Epoxy-Coated Steel Bars in Concrete Under Marine Environment - Cao, Hongfei; Lyu, Zhongda; Dong, Wei; Zhao, Zhuo; Gan, Weizhong; Wang, Yonggang (Frontiers in Materials, 2022)
Epoxy coating has been proven to protect steel bars from corrosion. However, the damage of epoxy coating is inevitable, and this may lead to more serious corrosion of steel bar. In order to study the corrosion resistance of steel bars with damaged epoxy coating, two groups of coating-damaged bar and one group of coating-intact rebar were designed, and six specimens were made. The influence of electrolyte concentration on the corrosion rate of steel bars was studied by setting different concentrations. After 30 days of accelerated corrosion, electrochemical data were recorded by the electrochemical workstation. The experimental result shows that the steel bars with coating damage have obvious polarization curve characteristics of corrosion, and corrosion resistance decreases obviously. According to the corrosion current and potential, the larger the damaged area of the coating, the faster will be the corrosion rate. According to the polarization curve data, the polarization resistance is modified, and the result is closer to the real polarization resistance value. The calculated corrosion rate shows that the corrosion rate of reinforcement is affected by both electrolyte concentration and coating damage area, and electrolyte concentration has a greater influence on the corrosion rate.